Processing light with an optically tunable mechanical memory - David P. Lake (Nature Portfolio, 2021)
The use of cavity optomechanics for optical information processing is hindered by mechanical dissipation and the difficulties in stored signal control. Here, the authors improve performances on both fronts using time-varying parametric feedback through an additional optical field in a multi-mode cavity.